Parcipatory action research for dengue control in Samarinda, Indonesia - Ridha, Muhammad Rasyid; Yudhastuti, Ririh; Juhairiyah, Juhairiyah; Garjito, Triwibowo Ambar; Aisyah, St.; Nisa, Khairatun; Agustina, Norsita (Intelektual Pustaka Media Utama, 2024)
Dengue control with community empowerment is the 1 house 1 larva monitor officer/Gerakan 1 Rumah 1 Jumantik (G1R1J). G1R1J is a national movement of community empowerment at the household level in an effort to reduce dengue This research aims to implement G1R1J through participatory action research. This research was conducted in Samarinda City, East Kalimantan, Indonesia with a participatory action research approach. The activities carried out were workshops, socialization, focus group discussions, and mentoring. The research evaluation was in the form of entomological surveys, namely before and after the activity. The important points of this research are that in the community independently Gerakan Emak-Emak Pembasmi Jentik Trisari (GEMATRI) has been formed, and the involvement of the village in the form of socialization and training, murals initiated by cadres, and training initiated by the village. At the policy level there is a decree of delegation of authority and budget for activities including dengue from the health office to the sub-district, but the public health center (Puskesmas) plays a role in providing assistance and counseling in the community. The larva-free index also increased from 50.67 to 66.43. We believe that the participation of the community, health cadres, and policy makers is very important to reduce the incidence of dengue hemorrhagic fever (DHF) in the future.